Improving Big Data Technologies with Visual Faceted Search - Najah Mahdi M.; Rahim Ahmad A.; Ismail R.; Subhi M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Advanced Analytics; Big data; Data visualization; Digital storage; Visualization; Big data applications; Complex searches; Data technologies; Document collection; End users; Exponential increase; Faceted search; Speed measurement; Search engines